PERUBAHAN FASE PERTUMBUHAN PADI SAWAH TADAH HUJAN SAAT EL NINO DI KABUPATEN GORONTALO - Ghinia Anastasia Muhtar; Intan Purwandhi (Jurnal Azimut, 2019)
This paper examines the impact of the El Nino climate on changes in the phase of rainfed lowland rice in Gorontalo Regency. To see the impact of the El Nino climate (in 2015) well, the year for the absence of El Nino (in 2016) is used as a comparison. Landsat 7 and landsat 8 images were used to analyze the growth phase of rainfed lowland rice by combining NDVI and TCT methods. The results of this study indicate that there has been a shift in cropping patterns resulting in a shift in the growth phase of rainfed lowland rice. Seen in September 2015 until October 2015, most of the wetland conditions were in fallow conditions, which then continued until February 2016, but the extent of fallow land conditions has been decreasing since January 2016 to February 2016. Unlike in September 2016 Until October 2016, most of the land was in stagnant conditions which showed farmers were preparing to plant rice. Finally in December 2016 until January 2017, the rice phase has been in the reproductive phase and maturation phase, whereas in El Nino years only in January 2016 to February 2016 are in the reproductive phase and maturation phase.